Analisis Interferensi Leksikal pada Wacana Koran Solo Pos April-Juni dan Implikasi dalam Pembelajaran - Sari, Intan Puspita; , Drs. Yakub Nasucha, M.Hum (2016)
The aims of this research are: 1) to understand the lexical interference and the causes factor of the discourse in the Solo Pos newspaper. 2) to design implications of the results of this study as a teaching material in the class XII SMA N 6 Surakarta. This research uses qualitative research methods. The object of this study is interference lexical discourse in Solo Pos newspaper edition April-June 2016 as a teaching material in the class XII SMA N 6 Surakarta. The technique of data collection which is use is see and record technique. The techniques of data analysis which is used in this research is the agih method, the data collected was studied and analyzed one by one carefully, making the core summary which consist of each data as same as the group. The results shows that 1) From the analyzed data, obtained by interference in the form of basic words as much as 8 data, interference lexical of compound words from several data sources which are analyzed by the researcher, there is no data included into lexical interference ofcompound words, and lexical interference form of word phrase is 3. 2) lexical interference discourse ofSolo Pos newspaper edition April-June, 2016 as a Indonesian teaching material in class XII SMA N 6 Surakarta includes of 11 analyzed data, generally have aninterference lexical form. It concludes that three variations of lexical interference, such as interference in the form basic words, lexical interference in theform of compound word, and interference in the form of word phrase which is the most dominant is the noun form. Key Words : interference, implications material, newspaper.